ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PARTISIPASI KERJA LANSIA DI KABUPATEN BULELENG - Cahyani, Made Intan Prawitasari; Dewi, Made Heny Urmila (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.04.TAHUN.2022DO - 10.24843/EEB.2022.v11.i04.p07, 2022)
This study aims to analyze the effect of education level, age, family income, and number of dependents simultaneously and partially on the work participation of the elderly in Buleleng Regency, as well as to determine whether the number of dependents plays a role in moderating the effect of family income on the work participation of the elderly population in Buleleng Regency. The method of determining the sample in this study used non-probability sampling with accidental sampling and purposive sampling with a sample size of 100 people. The data analysis technique used is the interaction test or Moderated Regression Analysis (MRA). Based on the results of the study, it was found that simultaneously education, age, household expenses, family income, and number,of dependent has a ‘significant’effect on, the ‘work participation,of, the,elderly population in Buleleng Regency. Partially education, age, and family income have a negative’and’significant, effect on the, work participation, of the elderly in Buleleng Regency, while’the number of dependents, partially has a positive and significant effect on the work participation of the elderly population in Buleleng Regency. The number of dependents strengthens the influence of family income on the work, participation ‘of’the elderly’population in Buleleng Regency